RELATIVE RISK OF ISLAMIC SUKUK OVER GOVERNMENT AND CONVENTIONAL BONDS (Global Journal of Management and Business Research, 2011)
Islamic bonds (sukuk) and conventional bond markets operate simultaneously in Malaysia complementing each other; the former operates on profit rates and the later on interest rates. In this paper we have analysed selected sukuks traded in Malaysia in terms of duration and convexity which are vital in deciding the market risk of fixed income bearing security. We compare these durations and convexities with that of government bonds and conventional bonds to assess the relative sensitivity of sukuk. Since the government bonds are highly liquid, without credit risk they stand better than sukuk. When compared with conventional bonds the sukuk stands better in these sensitivity measures. Interestingly the sukuk#x2019;s duration and convexities fall exactly in the middle between government and conventional bonds. The sukuk investor will get a better yield rate when compared to government bonds and lower rate when compared to conventional bonds. This information conveys that the Islamic sukuk is lesser risky than conventional bonds. Our findings are significant for the investors who are not investing in pure sukuk alone. The blend of government, Islamic and conventional bonds in a portfolio will bring down market risk and in addition will provide stable income above the government bonds.
Keywords: Riba; Islamic Sukuk; Bai Bithaman Ajil; Murabahah; Mudharabah; Duration; Convexity; Coupon Rate; Yield Rate